Pengaruh Usaha Mikro Kecil dan Menengah Dalam Mendorong Perekonomian Lokal di Era Digital di Kecamatan Masamba - Permata, Nely; Hapid; Badewi, Muhammad Hadis (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the impact of Micro, Small, and Medium Enterprises on the growth of the local economy in Masamba District within the context of the digital era. A quantitative approach was used through surveys conducted with local Micro, Small, and Medium Enterprises actors. The results indicate that digitalization has a positive effect on Micro, Small, and Medium Enterprises performance by enhancing market access, operational efficiency, and product promotion capabilities. The use of social media, e-commerce platforms, and digital payment systems emerged as key factors in expanding business reach. These findings highlight the strategic role of Micro, Small, and Medium Enterprises as the backbone of the regional economy and emphasize the importance of improving digital literacy and technological infrastructure. The study concludes that optimizing the digital-based role of Micro, Small, and Medium Enterprises can serve as a primary driver of local economic development in Masamba District.
Keywords: Micro; Small; Medium Enterprises; Local Economy; Digitalization; Masamba District